2012
DOI: 10.1111/j.1742-6723.2012.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of an extended care paramedic model in New Zealand

Abstract: We observed that ECPs have significant potential to reduce hospital ED attendances by treating more patients in the community, and this is associated with a low rate of subsequent ED presentations. Prioritisation of dispatch of ECPs to particular types of patients might be useful in maximising this reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Our review of titles and abstracts suggested that 138 articles might be eligible. After studying full texts, we confirmed that 13 papers 61,62,66,80,[89][90][91][92][93][94][95][96][97] reporting 12 studies met our inclusion criteria, as detailed in Figure 1. Table 4 summarises the 12 included studies; Tables 5 and 6 describe them in more detail and Table 7 assesses their quality.…”
Section: Inclusionmentioning
confidence: 56%
See 4 more Smart Citations
“…Our review of titles and abstracts suggested that 138 articles might be eligible. After studying full texts, we confirmed that 13 papers 61,62,66,80,[89][90][91][92][93][94][95][96][97] reporting 12 studies met our inclusion criteria, as detailed in Figure 1. Table 4 summarises the 12 included studies; Tables 5 and 6 describe them in more detail and Table 7 assesses their quality.…”
Section: Inclusionmentioning
confidence: 56%
“…The most common outcome measures were referrals made to a receiving unit or service, 66,89,[91][92][93]97 acceptance of referral by the patient 66,89,91,92,97 and patient conveyance following attendance by EMSs. 66,80,95 Five studies reported follow-up outcomes for patients receiving a novel intervention (see Table 6). 61,66,80,90,97 Three 66,80,90 used short follow-up periods (14 and 28 days) with limited inclusion of outcome measures in two, 80,90 whereas another collected physical health, quality-of-life and mortality outcomes.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations